2011
DOI: 10.5194/nhess-11-227-2011
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazard at the Western Mediterranean Spanish coast from seismic sources

Abstract: Abstract. Spain represents an important part of the tourism sector in the Western Mediterranean, which has been affected in the past by tsunamis. Although the tsunami risk at the Spanish coasts is not the highest of the Mediterranean, the necessity of tsunami risk mitigation measures should not be neglected. In the Mediterranean area, Spain is exposed to two different tectonic environments with contrasting characteristics. On one hand, the Alboran Basin characterised by transcurrent and transpressive tectonics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…Different tsunamis occurred on the Spanish coasts, they are more catastrophic and intense on the Atlantic than on the Mediterranean side (Álvarez-Gómez et al, 2011). In the western part of the Mediterranean area, there are historical disastrous tsunami events recorded.…”
Section: Storms or Tsunamis?mentioning
confidence: 99%
See 2 more Smart Citations
“…Different tsunamis occurred on the Spanish coasts, they are more catastrophic and intense on the Atlantic than on the Mediterranean side (Álvarez-Gómez et al, 2011). In the western part of the Mediterranean area, there are historical disastrous tsunami events recorded.…”
Section: Storms or Tsunamis?mentioning
confidence: 99%
“…The western part of the basin has also been reported as tsunamiexposed. Historic events have been reported from the Algerian coast, and tsunami propagation has been modelled (Álvarez-Gómez et al, 2011). Geomorphic evidence of ancient tsunami impacts has also been documented (Maouche et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a devastating event could be a magnitude 7.0 (or above) earthquake related to the rupture of the Carboneras fault or another seismogenic fault located in the Alboran Sea and along the northern African coast. The rupture of offshore fault segments could also generate a tsunami wave that would enhance the damage (Álvarez-Gómez et al, 2011). Probabilistic approaches would include the definition of hazard-consistent earthquake scenarios derived through hazard deaggregation.…”
Section: In the Seismic Hazard Evaluationmentioning
confidence: 99%
“…The ASTARTE programme examines ten test-sites where tsunamis occurred once or several times in the past: seven on the Mediterranean coast (Spain, France, Italy, Greece, Romania and two in Turkey), two on the Atlantic coast (Portugal and Morocco -the latter a nonEuropean country but nevertheless included in the programme) and one in the Norwegian Sea. Apart from the Lyngen site (Norway), all these sites are exposed to earthquake-related tsunamis (Álvarez-Gómez et al 2011) and several to eruptions of island volcanoes found in the Canaries and Greece. Tsunamis can also occur after underwater or subaerial landslides (Dawson et al 2004).…”
Section: Introductionmentioning
confidence: 99%